Réponses

2014-02-17T09:23:32+01:00
2(3x-4)²
=2(9x²-24x+16)
=18x²-48x+32

-2(3x-1)²     
=-2(9x²-6x+1)
=-18x²+12x-2 

7(3x-4)(3x+4)-(x+7)²       
=7(9x²-16)-(x²-14x+49)
=63x²-112-x²+14x-49
=62x²+14x-161

(x+3)²+(2x+7)²     
=x²+6x+9+4x²+28x+49
=5x²+34x+58

(2x+3)²-(4x-5)²
=4x²+12x+9-(16x²-40x+25)
=4x²+12x+9-16x²+40x-25
=-12x²+52x-16
2014-02-17T10:56:43+01:00
2 (3x-4)² = 2 ( 9x²- 24x +16 ) = 18x²- 48x + 32

-2(3x-1)²  = -2 (9x²-6x+1) = -18x²+12x-2 

7 (3x-4) (3x+4)-(x+7)² = 7 ( 9x²-16) - ( x²-14x+49 ) = 63x²-112-x²+14x-49 = 62x²+ 14x-161

( x+ 3)²+ ( 2x +7 )² = x² + 6x + 9 + 4x² + 28x + 49 = 5x² + 34x + 58

(2x+3)²-(4x-5)² = 4x² + 12x+9 - ( 16x²- 40x+25)=4x² + 12x+9-16x²+40x-25 =-12x²+52x-16

Bonne journée !